Survival outcomes of hepatic resections in Bismuth‐Corlette type IV cholangiocarcinoma. Issue 9 (15th December 2019) - Ku, Dominic; Tang, Reuben; Pang, Tony; Pleass, Henry; Richardson, Arthur; Yuen, Lawrence; Lam, Vincent
Abstract: Background: Surgical resection for Bismuth‐Corlette type IV (BC‐IV) hilar cholangiocarcinomas, also termed Klatskin tumours are technically challenging and were once considered unresectable tumours. Following advances in hepatobiliary imaging and surgical techniques, emerging evidence suggests that surgical resection is a viable avenue for long‐term survival. We aimed to identify factors affecting survival outcomes of hepatic resections for BC‐IV cholangiocarcinomas. Method: A systematic review was performed across multiple databases and several clinical trial registries. Two reviewers independently screened and selected papers that contained survival data on BC‐IV cholangiocarcinoma after hepatic resections. Results: Of 13 499 papers from our search result, 21 papers satisfied the inclusion criteria. The median post‐operative survival was 30.8 months. The average 1‐ and 5‐year post‐operative survivals were 61.6 and 33.3%, respectively. Predictors of long‐term survival included achievement of R0 margins, minimisation of operative time and reduction intra‐operative blood loss. Conclusion: Our analysis demonstrates improving post‐operative outcomes and survival in surgical resection of BC‐IV cholangiocarcinoma and suggests that radical surgical resection is a valid treatment option for the disease. Abstract : Our analysis demonstrates improving post‐operative outcomes and survival in surgical resection of BC type IV cholangiocarcinoma, and suggests that radical surgical resection is a valid treatment option for the disease.